ARTICULAR DAMAGE IN SJOGREN’S DISEASE - N S Shornikova; V I Vassiliev; A. V. Smirnov (Научно-практическая ревматология)
Objective. To give clinical and x-ray characteristics of joint syndrome in Sjogren's disease. Methods. 150 patients with Sjogren's disease were included. Clinical and retrospective radiological examinations were performed. Progression of hands and feet joints radiological damage was assessed using Larsen's scale. Results. Arthralgia was present in 76%, light morning stiffness - in 42,7% (more often lasting less then 20 min), Al the admission arthritis was noted in 16,7%. Hand small joints damage was prevalent. 36% of patients had history of arthritis. Its development was accompanied by purpura in one third of cases. Painful hand joint contractures were noted in 9,3%, diffuse hands oedema in 4,6%, ulnar deviation of the metacarpophalangeal joints in 0,7%, Jaccoud's arthropathy in 0,7%. Single surface erosions of hands were revealed at the X-ray examinations in 7 patients (4,7%). Early development of osteoarthrosis was noted. Larsen index ranged from 0 to 29 at the first and from 0 to 37 at the second examination (after 4.7 years). Conclusion. Joint syndrome in Sjogren's disease is characterized by light morning stiffness of short duration, arthritis which is usually not erosive and more often affects small joints оГ hands. Painful joint contractures and diffuse hands oedema are less frequent.